2021
DOI: 10.1016/j.ebiom.2021.103645
|View full text |Cite
|
Sign up to set email alerts
|

Time-dependent blood eosinophilia count increases the risk of kidney allograft rejection

Abstract: Background: Growing evidence suggest that type 2 immune effectors play a role in solid organ transplantation. The aim of this study was to evaluate the impact of blood count eosinophils (BCEo) on immunological outcomes in kidney transplant recipients with stable graft function after 3 months post-transplant. Method: We performed cause-specific Cox model considering BCEo, the use of calcineurin inhibitors and systemic corticoids as time-dependent explicative variables on a prospective cohort of 1013 kidney tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 62 publications
(71 reference statements)
0
4
0
Order By: Relevance
“…A recent cross-sectional study investigating kidney recipients diagnosed with ABMR found circulating anti-HLA IgE (with the same specificities as IgG) and identified in the graft deposits of IgE and the presence of mast cells and activated basophils ( 28 ). Moreover, another recent paper revealed that elevated eosinophil counts were associated with an increased risk of subsequent rejection and a trend to a higher incidence of de novo (IgG) DSA ( 44 ). While IgE was not analyzed, eosinophils are another hallmark of type 2 inflammation, thus these data also indirectly point to a role for Th2-driven immunity, including IgE in alloreactivity.…”
Section: Discussionmentioning
confidence: 99%
“…A recent cross-sectional study investigating kidney recipients diagnosed with ABMR found circulating anti-HLA IgE (with the same specificities as IgG) and identified in the graft deposits of IgE and the presence of mast cells and activated basophils ( 28 ). Moreover, another recent paper revealed that elevated eosinophil counts were associated with an increased risk of subsequent rejection and a trend to a higher incidence of de novo (IgG) DSA ( 44 ). While IgE was not analyzed, eosinophils are another hallmark of type 2 inflammation, thus these data also indirectly point to a role for Th2-driven immunity, including IgE in alloreactivity.…”
Section: Discussionmentioning
confidence: 99%
“…CCL11 may also attract T cells and macrophages in addition to eosinophils and enable the recruitment of more inflammatory cells into the graft. Altogether, a triple connexion would be easily postulated between CCL11, CCR3 and eosinophils with allograft rejection [55] [56]. However, in human heart transplants, CCR3 expression was studied in endomyocardial biopsies and it was found to be most intense at sites of focal T cell infiltrates and was associated non-significantly with acute rejection [28], while CCR3 mRNA was described as absent in acute rejection biopsies in human renal transplants [20].…”
Section: Discussionmentioning
confidence: 99%
“…In addition eosinophils express CD154 and the number of eosinophils in circulation are a biomarker of solid organ transplant rejection ( 44 , 103 ). Activated Basophils express CD154, IL4 and IL13 and induce B cell expression of IgE ( 43 ).…”
Section: Discussionmentioning
confidence: 99%